If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9m + (-6) = 93 -9m + -6 = 93 Reorder the terms: -6 + -9m = 93 Solving -6 + -9m = 93 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -9m = 93 + 6 Combine like terms: -6 + 6 = 0 0 + -9m = 93 + 6 -9m = 93 + 6 Combine like terms: 93 + 6 = 99 -9m = 99 Divide each side by '-9'. m = -11 Simplifying m = -11
| 2=yx+x | | f(x)=100(0.7) | | r/2+8=9 | | 2=yx+y | | 16-3x+5x=180 | | 7m+2m+8m-6= | | .95=logx | | 55*1=n | | 5x-16+3x=180 | | 4x-12=6x-36+14 | | -3x+12= | | -9f+(-32)=-95 | | 3+2h=5 | | 2n+7-7n=33-11n+10 | | 3+-1u=0 | | 2t-4t=8 | | 8g-15=73 | | 1+-4u=0 | | 8c-(-19)=59 | | s=6*7+64t-16t^2 | | 1.5(9x-3)=-4+8x | | h+30=180 | | 8c-(-19)=58 | | 5x+3=-x-2 | | -8+2g=-2 | | 5x+5=-10forx | | 2(w+5)=12 | | 4(x-a)+5b=5x+aforx | | ps+qr=r | | 15-5y=y+11+3y | | X+7=3x+11 | | 2x-(3+4x)=7 |